Molecular typing of Staphylococcus aureus collected from a Major Hospital in Amman, Jordan - Bazzoun, Dana A; Harastani, Houda H; Shehabi, Asem A; Tokajian, Sima T (Journal of infection in developing countries, 2014)
Introduction: Over the past decade methicillin-resistant Staphylococcus aureus (MRSA) has been recognized as a major cause of healthcare associated infections. Recently, however, epidemiology of this pathogen has changed drastically with the emergence of new clones in the community. Efficient epidemiological typing methods are essential to monitor and limit the occurrence and spread of epidemic clones. Methodology: A total of sixty S. aureus isolates were collected from the Jordan University hospital in Amman-Jordan. All isolates were characterized using Staphylococcus protein A (spa) typing and pulsed-field gel electrophoresis (PFGE). Samples were tested for their susceptibility patterns against seven antimicrobial agents and for their potential to form biofilms. Results: spa typing showed that spa type t044 was the most common representing 28% of the isolates studied and 38% of the MRSA population. PFGE revealed fourty-six pulsotypes among the sixty tested isolates clustering similar spa types together. The predominant resistance was detected against levofloxacin, chloramphenicol and clindamycin. One MSSA isolate typed as spa t955 showed biofilm formation potential through protein deposition.. Conclusion: The study results are based on one hospital, but the findings of this and other studies conducted in the region indicate that there is an urgent need for standardized surveillances combined with the application of well-validated typing methods to assess the occurrence of MRSA and to control its spread.